Ordinary Irish life : music, sport and culture - Fhuartháin, Méabh Ní; Doyle, David M. (Irish Academic Press, 2013)
Drawing together the strands of music, sport, and popular culture under the umbrella of 'Ordinary Life, ' this engaging new book takes the reader on an entertaining journey through modern Ireland, celebrating the many unique expressions of 'Irishness.' From the folk roots of popular culture in the song The Night Larry Was Stretched, to the showbands and community building among U2 fans; from the Riddle of Ravenhill and the 1954 Irish Rugby International, to The Lion of Lahinch - an IRA man's appearance at the Walker Cup. Everyday life is explored in Corner Boys in Small Town Ireland, while a.